"Bewitching" or confusing methaphysics? The demarcation between science and metaphysics according to Karl Popper - Botha, M. Elaine (Koers, 1986)
The problems of both classical and modern theory of knowledge, according to Popper, reside in the problem of demarcation: a problem closely re lated to the problem of induction. The paper argues the view that Popper's view of metaphysics is ambiguous, requiring another criterion to distinguish between "good " and "bad " metaphysics. The sources of the problem are pinpointed, and Popper's distinction between three types of theory outlined. The article then explores the distinction between types of theories and the issues of falsification, testability and refutation, before going on to a consideration of the relationship between science and metaphysics, and w eighing up the issue of good ancid metaphysics. From this emerges clearly that the second "criterionot demarcation" is needed to make precisely this distinction; also in view of Popper's u n clear, even ambiguous, view of metaphysics.